2015
DOI: 10.1155/2015/620643
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and Radiotherapy versus Radiotherapy Alone in High Grade Gliomas: A Very Long Term Comparative Study and Literature Review

Abstract: Temozolomide (TMZ) is the first line drug in the care of high grade gliomas. The combined treatment of TMZ plus radiotherapy is more effective in the care of brain gliomas then radiotherapy alone. Aim of this report is a survival comparison, on a long time (>10 years) span, of glioma patients treated with radiotherapy alone and with radiotherapy + TMZ. Materials and Methods. In this report we retrospectively reviewed the outcome of 128 consecutive pts with diagnosis of high grade gliomas referred to our instit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…Therefore, it is essential to develop more effective therapeutic regimens for GBM treatment. To identify novel targets to improve the current chemotherapeutic regimens, we performed expression profiling of chemo-sensitive (U87) and resistant (T98) GBM cell lines treated with TMZ, the first-line treatment for GBM 19 . Among the fourteen genes found to be substantially regulated in TMZ-treated U87 cells, GADD45A was identified in both the cell cycle and apoptosis arrays.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is essential to develop more effective therapeutic regimens for GBM treatment. To identify novel targets to improve the current chemotherapeutic regimens, we performed expression profiling of chemo-sensitive (U87) and resistant (T98) GBM cell lines treated with TMZ, the first-line treatment for GBM 19 . Among the fourteen genes found to be substantially regulated in TMZ-treated U87 cells, GADD45A was identified in both the cell cycle and apoptosis arrays.…”
Section: Discussionmentioning
confidence: 99%
“…The previous study revealed that TMZ administration combined with radiotherapy has good efficacy for a patient with glioblastoma multiforme. 5…”
Section: Chemotherapy For Gliomamentioning
confidence: 99%
“…During DNA replication, methylated guanine will couple with thymidine (which should be coupled with cytidine) thus cause mismatch repair and induce apoptosis. 5,7 These cellular repair mechanisms are dysfunctional and lead to apoptosis. 8 Bioavailability of oral TMZ is 100% and possesses good penetration through blood-brain barrier as well as brain tumor tissue.…”
Section: Temozolomide As Treatment For Gliomamentioning
confidence: 99%
See 1 more Smart Citation
“…It should however be stressed that using combination therapy in patients with brain tumours increases the chances of an ever longer survival. An example is afforded by patients suffering from glioblastoma multiforme (glioblastoma), where the combination of surgical treatment with adjuvant chemoradiotherapy improves local control (LC) and extends overall survival (OS) [2]. At the same time, patients undergoing antineoplastic therapy are more likely to suffer from worsening psychomotor dysfunction.…”
Section: Introductionmentioning
confidence: 99%